Design of aerobatic aircraft wing - Potter, J. G. (Cranfield University, 1969)
The aircraft under consideration in the following text is a swing wing, 50,000 lb. (maximum weight), land based strike aircraft. The various roles of the aircraft are strike operations at a Mach number of 2.0 and height 36,000 feet or Mach number of 0.9 at low level, interceptor operations at a Mach number of 2.0 with a, dash at a Mach number of 2.0 and search and patrol operations at a Mach number of 0.76 and a height of 36,000 feet (with wings unswept). Design of the aircraft was split into several sections each one being investigated by a different student. The section analysed in this report being the forward-centre fuselage. This lies between the rear sloping pressurised bulkhead of the cockpit to the aft bulkhead of number two fuel tank. Time did not allow for the design of all the structural parts but detailed studies were conducted on two different frames (one light fabricated and one heavy machined), the nose undercarriage bay, two sections of fuselage cross-section, and the variable geometry bullet including aerodynamic loading in the intake. A sample fatigue calculations were done on a fuel tank and nose undercarriage together with a complete weight breakdown for the forward-centre fuselage (several approximations being made 'for undersigned structure). From the loading calculations the critical cases defined that the structure in this section of the fuselage was designed on the manoeuvres and landing cases. Use of Concorde material (aluminium alloy) RR. 58 was used wherever possible because of temperature effects in the high speed configuration. However, for some of the view heavily loaded members steel had to be used (with the appropriate temperature reduction factor applied to the allowable stresses) to keep the volume of material to a minimum.